EGb761 attenuates depressive-like behaviours induced by long-term light deprivation in C57BL/6J mice through inhibition of NF-κB-IL-6 signalling pathway - Yongdong Zhang; Yuehan Zhao; Fang Pan; Panmin Zhang (Central European Journal of Immunology)
Our previous investigation found that Ginkgo extract EGb761 could attenuate the depressive-like behaviours induced by a single injection of lipopolysaccharide in mice. However, it has not been investigated whether EGb761 is effective on depressive-like behaviours induced by long-term light deprivation and whether its effects are associated with the inhibition of NF-κB-IL-6 signalling pathway. In this study, three groups (vehicle group, EGb761 low-dose group, and EGb761 high-dose group) of C57BL/6J male mice were exposed to constant darkness for four weeks. The control mice remained on a 12 : 12 light-dark cycle. Depressive-like behaviours were evaluated by tail suspension test (TST), forced swim test (FST), and sucrose preference test (SPT). Spontaneous locomotor activity was evaluated by open field test (OFT). Levels of IL-6, IL-6 mRNA, NF-κB p65, phospho-NF-κB p65, IκBα, and phospho-IκBαwere measured using Elisa, western blotting, or PCR assays. NF-κB p65 DNA binding activity was evaluated using Chemi Transcription Factor Assay Kit. Results showed long-term light deprivation prolonged the immobile time in TST and FST, shortened the latency to immobility in FST, reduced spontaneous locomotor activity in OFT, decreased sucrose preference in SPT, and increased levels of IL-6, IL-6 mRNA, NF-κB p65, phospho-NF-κB p65, and phospho-IκBα in hippocampal tissue. EGb761 dose-dependently reversed the changes of the above parameters induced by long-term light deprivation, without affecting spontaneous locomotor activity. We conclude that EGb761 could attenuate the depressive-like behaviours and inhibit the NF-κB-IL-6 signalling pathway in a light-deprivation-induced mouse model of depression.